Design, Synthesis, and Biological Evaluation of Novel Peptide Gly3‐MC62 Analogues as Potential Antidiabetic Agents. (25th April 2015) - Yang, Baowei; Zhang, Chenyu; Li, Xue; Yan, Sijia; Wei, Wei; Wang, Xuekun; Deng, Xin; Huang, Wenlong; Qian, Hai
<x xml:space="preserve">Abstract</x> Two series of conformationally constrained analogues from Gly3‐MC62 were designed by scanning the residues Lys1, Thr2, Met4, Lys5, Met7, and Ala8 with an i‐(i + 2) lactam bridge consisting of a Glutamic acid–xaa–lysine (Glu–Xaa–Lys) scaffold and a diproline fragment. They were synthesized and evaluated for their antihyperglycemic effects. Through screening in normal and mice with diabetes mellitus, peptides II‐5, III‐3, III‐4, and III‐5 showed significant improvement in antihyperglycemic and antioxidative activities compared with Gly3‐MC62, especially the compound III‐4. The primary mechanism of the compounds (II‐5, III‐3, III‐4, and III‐5) underlying this effect is the islet β‐cells against oxidative damage induced by STZ, and III‐4‐treated mice showed considerable improvement in the preservation of beta cells in the pancreatic islets of DM mice. These data suggested that III‐4 could be candidate for the future treatment of diabetes mellitus.